Pengaruh Media Stik Es Krim Terhadap Motivasi Belajar Matematika Materi Bilangan Bulat - Sari, Waliyyu Friska; Hermansah, Bambang; Ayu, Imelda Ratih (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The problem in this study is that in the process of learning mathematics students more often play or chat with classmates than pay attention to the teacher's explanation, it is also caused by teachers who still use conventional methods. In addition, during the learning process, teachers also use less learning media that attract the attention and interest of students. This study aims to determine whether there is an influence of ice cream stick media on the motivation to learn mathematics integer material grade IV SD Negeri 139 Palembang.The method used in this study is an experimental / quantitative method by comparing before and after treatment. The results of the study were carried out through three aspects of testing, namely the normality test, homogeneity test, and t test. In the normality test, the results in the experimental class and control class were normally distributed because the experimental pretest values p > a or 0.200 > 0.05 and the control pretest p > a or 0.136 > 0.05 while the experimental posttest values p > a or 0.084 > 0.05 and the control posttest p > a or 0.200 > 0.05. Then the homogeneity test result data was obtained that the students' prestest and posttest scores had a signification based on mean of 0.285. In other words, it can be concluded that the results of the data on pretest scores and posttest scores of students are homogeneous because p > a or 0.285 > 0.05. So the data from the independent sample test with the help of using SPSS 29, researchers concluded that there was a significant influence on the use of ice cream stick media on the motivation to learn mathematics integer material grade IV SD Negeri 139 Palembang with a sig value of 0.001 < 0.05.